Sistema de monitoramento baseado em identificação por radiofrequência (RFID) para cadeia fria farmacêutica - Santos, João Carlos Silva dos (2015)
The healthcare has several goods that require special care, which include a correct handling in monitored and controlled environment throughout the production, transport and storage processes. Among these goods we can highlight temperaturesensitive drugs, which need to be kept cold throughout the whole process until be administered to the patient. These precautions are extremely important to maintain the physical and chemical integrity of the medication, preventing unnecessary waste due to its deterioration or inactivation, and avoiding possible damage to the patient. This work proposes the development of a monitoring system for the pharmaceutical cold chain based on RFID to be used during transport and storage of drugs prior to administration in patients. The system consists of RFID readers, passive tags, semi-passive tags coupled with sensors (BAP tags), a database and a remote web server. To colaborate with the system conception, a BAP tag was developed to monitor temperature conditions during transport and storage of products, using ultra-low power techniques and smart memory management. The results demonstrate that the developed BAP tag consumes only 0.1 uA in Sleep mode and 3.28 uA in Active mode, it has a high sensitivity of -27 dBm and it can store up to 32.7 k temperature samples in a 128 kbits memory. With this consumption profile, BAP tag can continuously monitor temperature for up to 7 years without battery replacement with a 5 minute sampling interval. In addition to the BAP tag, two software for RFID readers have been developed for use in conjunction with the mentioned BAP tag, sending the monitoring data to the remote server.